2009
DOI: 10.1007/s00213-009-1488-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ethanol drinking-in-the-dark by mecamylamine and nicotinic acetylcholine receptor agonists in C57BL/6J mice

Abstract: Rationale-Recent reports describe a restricted access ethanol consumption paradigm where C57Bl/6J mice drink until intoxicated. Termed "drinking in the dark" (DID), this paradigm has been used as a model of binge drinking. Although neuronal nicotinic acetylcholine receptors (nAChRs) have been implicated in alcohol drinking in rats pre-trained to self-administer ethanol, their role in binge-like ethanol consumption is unknown.Objectives-To determine if nAChRs are involved in binge drinking as measured by the DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 42 publications
(52 reference statements)
11
120
0
1
Order By: Relevance
“…Local injection of mecamylamine into the VTA reduces rat operant responding for EtOH and EtOH-associated cues, as well as consumption during relapse [19,20] . Mecamylamine delivered systemically reduces EtOH consumption in C57Bl/6J mice in restricted access EtOH consumption "drinking in the dark" (DID) paradigm [21] , a model of binge drinking, as well as in the two-bottle choice consumption assay [22] . More recently, it has been demonstrated that mecamylamine blocks EtOHmediated activation of VTA DAergic neurons in mouse midbrain slices [23] .…”
Section: Impact Of Nachrs In Etoh Reward and Dependencementioning
confidence: 99%
“…Local injection of mecamylamine into the VTA reduces rat operant responding for EtOH and EtOH-associated cues, as well as consumption during relapse [19,20] . Mecamylamine delivered systemically reduces EtOH consumption in C57Bl/6J mice in restricted access EtOH consumption "drinking in the dark" (DID) paradigm [21] , a model of binge drinking, as well as in the two-bottle choice consumption assay [22] . More recently, it has been demonstrated that mecamylamine blocks EtOHmediated activation of VTA DAergic neurons in mouse midbrain slices [23] .…”
Section: Impact Of Nachrs In Etoh Reward and Dependencementioning
confidence: 99%
“…It has been reported that partial agonists at ␣ 4 ␤ 2 nAChRs, in predicted free human brain concentrations, could desensitize the nAChRs followed by minimal activation, thereby generating a response similar to that of an . Pretreatment with cytisine reduces ethanol-induced DA and DOPAC content in ventral striatum either by its low intrinsic efficacy (partial agonist) or desensitization of nAChRs [26] . On the other hand, lobeline is a non-selective antagonist at nAChRs and reduces the ethanol-induced increase in DA and DOPAC content likely by functional blockade of nAChRs in VTA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cytisine is a nicotinic alkaloid and a known partial agonist at ␣ 4 ␤ 2 and full agonist at ␣ 7 nAChRs [23,24] . Cytisine has shown potential as a smoking cessation treatment [25] , and cytisine or its derivatives have been found to inhibit ethanol intake and ethanol-seeking behavior in rodent models [21,26,27] . However, the neurochemical effects of cytisine on ethanol-induced DA function remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…These receptors have been identified as promising targets for the treatment of several neurological disorders, such as Parkinson's and Alzheimer's diseases, Tourette's syndrome, dyskinesias, schizophrenia, anxiety, attention deficit disorder, and pain [4][5][6]. Additionally, this natural compound was found to decrease nicotine-induced extra cellular dopamine release in the nucleus accumbens [7], and was shown to reduce ethanol drinking behaviors in mice or rats [8,9] and ethanol-induced dopamine and its metabolite [10]. Therefore, nicotinic ligands could be developed as potential therapeutic candidates for binge-like ethanol drinking and dependence in humans.…”
Section: Introductionmentioning
confidence: 99%